2009
DOI: 10.1182/blood-2009-04-218636
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Kindlin-3 in LAD-III eliminates LFA-1 but not VLA-4 adhesiveness developed under shear flow conditions

Abstract: Leukocyte adhesion deficiency (LAD)-III is associated with homozygous stop codon mutations in Kindlin-3, the hematopoietic member of the Kindlin family of integrin coactivators. In addition, a subgroup of LAD-III patients has a homozygous splice junction mutation in and reduced expression of the Rap-1 guanine nucleotide exchange factor, CalDAG-GEFI (CDGI). In this study, we compared the adhesive properties of the leukocyte function-associated antigen-1 (LFA-1) and very late activation antigen-4 (VLA-4) integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 47 publications
8
105
1
Order By: Relevance
“…Despite this efficient arrest of Kindlin-3-deficient effector T cells at high VCAM-1 levels, firm adhesion on recombinant VCAM-1 and endothelial cells was reduced. These findings are in line with a previous report showing that chemokine-stimulated Kindlin-3-deficient LAD-III effector T cells show transient adhesion, but not stable adhesion, to VCAM-1 under flow conditions (28). Furthermore, these findings suggest that α4β1 on Kindlin-3-deficient effector T cells can adopt an affinity state sufficient for the production of weak α4β1-VCAM-1 interactions.…”
Section: Discussionsupporting
confidence: 82%
“…Despite this efficient arrest of Kindlin-3-deficient effector T cells at high VCAM-1 levels, firm adhesion on recombinant VCAM-1 and endothelial cells was reduced. These findings are in line with a previous report showing that chemokine-stimulated Kindlin-3-deficient LAD-III effector T cells show transient adhesion, but not stable adhesion, to VCAM-1 under flow conditions (28). Furthermore, these findings suggest that α4β1 on Kindlin-3-deficient effector T cells can adopt an affinity state sufficient for the production of weak α4β1-VCAM-1 interactions.…”
Section: Discussionsupporting
confidence: 82%
“…5), suggesting the important role of kindlin-3 in triggering extended (high affinity) conformation of ␣4 integrins. The results are consistent with previous reports that kindlin-3 is required for the induction of the high affinity conformation of ␣L␤2 (31,59). Interestingly, kindlin-3 has been shown to have little effect on the affinity of purified monomeric ␣IIb␤3 integrin in a cell-free system (60).…”
Section: Discussionsupporting
confidence: 82%
“…Previous study shows that ␣4␤1 in kindlin-3-null lymphocytes retains intrinsic rolling adhesions to VCAM-1 and exhibits partial defects in chemokine-stimulated adhesiveness to VCAM-1 (31). Moreover, it has been reported that kindlin-3-deficient lymphocytes, although deficient in optimal firm adhesions, still are able to use their residual integrin adhesiveness to enter tissues (50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations